The Association Between Knowledge and Vulvar Hygiene Practices Among Adolescent Girls - Pransiska, Widia; Miden, Destinady K.; Annah, Itma; Migang, Yena Wineini (SIGn Journal of Public Health, 2025)
Adolescent reproductive health requires critical attention due to the high prevalence of reproductive tract infections, such as pathological leukorrhea, which are frequently triggered by poor intimate hygiene. This issue is exacerbated by inadequate health literacy among adolescents, posing long-term health risks. This study aimed to analyze the association between reproductive health knowledge and vulvar hygiene practices among adolescent girls at a senior high school in Central Katingan, Indonesia. A quantitative, descriptive-analytic study with a cross-sectional design was conducted involving 110 respondents selected via simple random sampling. A structured questionnaire was used to measure knowledge and practices, followed by descriptive statistics and cross-tabulation. The results indicated that the majority of respondents demonstrated good knowledge (66.40%) and good vulvar hygiene practices (59.10%). Data analysis revealed a consistent positive association: students with strong knowledge generally exhibited adequate hygiene practices. However, a discrepancy was identified among a subset of respondents who possessed adequate knowledge but did not demonstrate ideal practices, suggesting potential barriers related to motivation or facility access. In conclusion, while knowledge serves as a fundamental basis for establishing preventive practices, interventions focusing solely on cognitive aspects are insufficient. This study recommends implementing holistic health education programs that integrate family support and utilize technology-based visual media. This approach ensures the sustainable internalization of hygiene values, thereby effectively reducing the risk of reproductive morbidity among adolescents.